2003
DOI: 10.1039/b308117f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sulfur, selenium and tellurium catalysts with antioxidant potential

Abstract: Oxidative stress is implicated, either directly or indirectly, in the pathology of a range of human diseases. As a consequence, the development of efficient antioxidants for medical use has become increasingly important. We have synthesised a range of structurally related organo-sulfur, -selenium and -tellurium agents and demonstrated that a combination of electrochemical methodology, in vitro assays and cell culture tests can be used to rationalise the antioxidant activity of these catalytic agents. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…[37] The interaction of selenium (and tellurium) compounds with MT and GSH reveals a potential role for these in the development of novel therapeutic agents with zinc-releasing and antioxidant properties. [38,39] Specifically, selenium may be incorporated into proteins in the form of selenocysteine (Sec) and nonspecifically as selenomethionine. [40] It may therefore be possible to design and synthesize therapeutic agents and enzymes in which sulfur atoms are replaced by Se.…”
Section: Involvement Of Seleniummentioning
confidence: 99%
“…[37] The interaction of selenium (and tellurium) compounds with MT and GSH reveals a potential role for these in the development of novel therapeutic agents with zinc-releasing and antioxidant properties. [38,39] Specifically, selenium may be incorporated into proteins in the form of selenocysteine (Sec) and nonspecifically as selenomethionine. [40] It may therefore be possible to design and synthesize therapeutic agents and enzymes in which sulfur atoms are replaced by Se.…”
Section: Involvement Of Seleniummentioning
confidence: 99%
“…Therefore, inhibition of the PN-mediated nitration and oxidation reaction is very essential. Sies et al, have reported several sulphur and selenium containing small molecules which are efficient inhibitor of PN-mediated nitration and oxidation reactions [37]. As many of the selenides and spirodiazaselenuranes react effectively with peroxides, we extended our work to investigate the effect of different substituents on the PN-scavenging antioxidant activity.…”
Section: Inhibition Of Peroxynitrite-mediated Nitration and Oxidationmentioning
confidence: 98%
“…The compound was purified in column chromatography using petroleum ether and ethyl acetate as eluents. Yield: 82%, (37): To a stirred solution of 36 (0.13 mmol) in dry CH2Cl2 (5 mL), hydrogen peroxide (0.13 mmol) was added. The reaction mixture was stirred for 4 h at room temperature.…”
Section: General Synthesis Of Spirodiazaselenuranesmentioning
confidence: 99%
“…An increase in the concentrations of oxidizing species would destroy cellular redox balance and lead to the oxidation of proteins, DNA, membrane lipids, and thus mitochondrial dysfunction and ultimately cell death [36]. Anti-oxidative enzymes, such as superoxide dismutase, catalase, and GPx, are the three major reactive oxygen species scavengers in cells and hence protect cells against oxidative damage.…”
Section: Discussionmentioning
confidence: 99%